Metamorphoses of Friendship: Jacques Derrida and Saint Augustine - Julien, Jacques (Religions, 2024)
In his Circumfession, Jacques Derrida journeys at length with Saint Augustine. The angle adopted is somewhat autobiographical, its philosophy staying as close as possible to the body, to the intimate, to the family. In Politics of Friendship, the Bishop of Hippo is one interlocutor among others. Once again, the autobiographical vein is kept alive, this time by book IV of Augustine’s Confessions. The episode of private life, the dear friend’s death, opens now onto political dimensions. Saint Augustine plays a pivotal role in what Derrida calls the infinitization of friendship. Over time, links were put in place, and the contemporary society cannot ignore or get rid of them. Our work here goes back to the traces left in the writings of Saint Augustine by the most classic canons of friendship incorporated into Christian theology. In our conclusion, we will see that Derrida puts this tradition in tension with fraternity, family, and community—all elements that the philosopher considers the most problematic in our current situation, and even more so for a democracy to come.